ЎЗБЕК МУМТОЗ АДАБИЁТИДА ҲИКМАТНАВИСЛИК АНЪАНАСИ (Scientific journal of the Fergana State University, 2023)
The existence of hikmat tradition under influence of “Divani hikmat” by Ahmad Yassaviy in Uzbek literature is scientifically substantiated in the thesis